A "Rua-Pátio" e a caracterização dos espaços livres de edificação das novas Vilas Paulistanas - Aragão, Solange (Paisagem e Ambiente, 2000)
The open spaces of the newest villas of São Pauio differ, in some aspects, from those of the oldest ones. On the other hand, architects and constructors are always trying to bring back some characteristics and uses of the villas built in this city in the past. While the villas of the beginning and the middle of the 20th century used to have a narrow street that led to a courtyard surrounded by the houses, the villas of the 90s have one larger street with some characteristics of a courtyard. Therefore, we call it a "courtyard street ". Some elements - such as fountains and lampposts - which supposedly remind people of the oldest villas, are located in this open space - that it is intended to be a social space. We aim here to define the "courtyard street" and to analyse the open spaces of the newest villas of São Pauio and their uses